2010
DOI: 10.1177/0170840610387237
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Derailment or the End of the Line? Managers Coping with Unemployment at 50

Abstract: Based on fieldwork conducted at the outset of the 2008 economic downturn, this paper examines the experiences of a group of unemployed managers and professionals in their fifties. Following a review of existing literature, the authors use a narrative methodology to explore how these people incorporate the experience of job loss into their selfimages and identities. They identify certain core similarities in the experiences of unemployed professionals and then discern three narrative strategies through which un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 60 publications
1
102
2
Order By: Relevance
“…The episodic interview yields context-related presentations about particular experiences that the interviewee remembers in the form of a narrative. Routine phenomena, such as job loss (Gabriel et al, 2010), can be explored with episodic interviewing as it invites respondents to examine their everyday knowledge about a meaningful issue (Flick, 2014). This allows the researcher to compare the knowledge of interviewees from different social groups, that is, as a social representation (Flick, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The episodic interview yields context-related presentations about particular experiences that the interviewee remembers in the form of a narrative. Routine phenomena, such as job loss (Gabriel et al, 2010), can be explored with episodic interviewing as it invites respondents to examine their everyday knowledge about a meaningful issue (Flick, 2014). This allows the researcher to compare the knowledge of interviewees from different social groups, that is, as a social representation (Flick, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Ezzy, 2000) and narrative approaches have been used in such studies (e.g. Gabriel, Gray, & Goregaokar, 2010). These inquiries, however, tend to examine the perceptions of managerial and professional employees (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has consistently shown unemployment to be a highly traumatic event, characterized by feelings of shock, loss, and extreme distress (Cottle, 2003;Darity & Goldsmith, 1996;Gabriel, Gray, & Goregaokar, 2010;Madonia, 1983;Paul & Moser, 2009;Schneer, 1993;Wanberg, 2012). Garrett-Peters (2009) argues that unemployment can create a sense of rupture in identity that assaults the deepest aspect of self.…”
Section: Unemployment As a Source Of Traumamentioning
confidence: 99%